The academic medicine handbook : a guide to achievement and fulfillment for academic faculty - Roberts, Laura Weiss (Springer New York, 2013)
Attaining professional success and finding personal happiness in academic medicine is not an easy path, yet both are critical if the future is to be brighter through better science, better clinical care, better training, better responsiveness to communities, and better stewardship and leadership in the health professions.  This concise, easy to read title consists of "mini" chapters intended as a resource to assist early- and middle-career physicians, clinicians, and scientists in understanding the unique mission of academic medicine and building creative, effective, and inspiring careers in academic health organizations.  Organized in eight sections, the Guide covers such areas as finding your path in academic medicine, getting established at an institution, approaching work with colleagues, writing and reviewing manuscripts, conducting empirical research, developing administrative skills, advancing your academic career, and balancing your professional and personal life.  Each chapter includes pointers and valuable career and "best practices" strategies in relation to the topic area.  An exciting addition to the professional development literature, Achievement and Fulfillment in Academic Medicine: A Comprehensive Guide is an indispensable resource for anyone seeking to achieve a fulfilling career in academic medicine.